Tigers Are Not Afraid (López, 2017). Lloronas against the femi-genocidal order - Alarcon Zayas, Violeta (Comunicación y Género [Communication and Gender], 2023)
The "traumatic grotesque" concept (Connelly, 2015) will serve as the basis for the discourse analysis of the functioning of the phantasmagoric female in the film Vuelven (López, 2017), figure that connects with the myth of La Llorona. In order to investigate its function as a critical device, the elements with which the critical gender perspective is built from terror and abjection will be unraveled, from the concepts of "precarious lives" (Butler, 2006) and "femi-genocides" (Segato, 2016) in the context of “gore capitalism” (Valencia, 2010). We conclude that the grotesque traumatic metaphor shows the spectral as an ambivalent ally that terrifies and disorients, but that reveals the corrupt and violent sociopolitical framework of the feminicidal patriarchal order, and dignifies its victims.